The influence of normal curing temperature on the compressive strength development and flexural tensile behaviour of UHPFRC with vipulanandan model quantification. (April 2021) - Hassan, A.M.T.; Mahmud, G.H.; Mohammed, A.S.; Jones, S.W.
Abstract: Ultra-high performance fibre reinforced concrete (UHPFRC) specimens were cast and cured at temperatures of 10, 20, 30, and 90 °C for periods of up to 360 days to investigate the long-term strength development. The influence of the three lower curing temperatures on the compressive and flexural tensile strengths and behaviour of UHPFRC was studied and compared to the results of 90 °C cured specimens. The results indicated compressive and flexural tensile strengths development at an early age were highly dependent on the curing temperature. The 90 °C cured specimens reached maximum compressive and flexural strengths within 7 days of casting. Specimens from the lower curing temperatures reached feasible striking compressive strengths (greater than 45 MPa) within 3 days of casting and achieved similar strengths to the 90 °C specimens after 90 days. Furthermore, various models such as the Vipulanandan model are developed to predict and correlate various mechanical properties of UHPFRC for any curing temperature, age and steel fibre content.